Preliminary investigation of the eruption time of kimberlite in the Late Devonian in Mengyin, Shandong - Tian, Ruicong; Wang, Haiqin; Tian, Jingxiang; Shan, Wei; Wang, Xiufeng; Chi, Naijie; Ma, Xiaodong; Chu, Zhiyuan; Li, Shenghu; Lv, Qing (Frontiers in Earth Science, 2023)
Kimberlite in the Mengyin area is acted as a good carrier for studying the properties and material evolution of Paleozoic mantle. In situ carbonate U-Pb dating of the kimberlite in the Mengyin area has been carried out, the age of primary calcite in kimberlite was constrained at 383±18Ma (MSWD=6.6), which indicates that the kimberlite eruption occurred at this time, and the limestone xenolith underwent thermal alteration to form marble. This suggests that the thinning of the lithosphere occurred at least after the late Devonian. Fluid inclusions reveal that the formation temperature of the marble is 243-370℃, salinity is 2.57-14.77% (NaCl), pressure is 3.22-20.70 MPa, and depth is mainly 900-1000m. The overall denudation depth in the west Shandong area since the late Devonian is 900-1000m, and the overall crustal rise rate is 3m/Ma.